PENGARUH INFORMASI KEUANGAN TERHADAP ABNORMAL RETURN SAHAM SESAAT SEBELUM LAPORAN KEUANGAN TERBIT - Raihan, Muhammad Irza; Ardiansyah, Ardiansyah (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to find out and prove empirically the effect of financial information in the form of a ratio to abnormal returns on company shares just before the financial statements are published for companies listed on the Indonesia Stock Exchange (IDX) with the research periods of 2012, 2015 and 2017. This study used a purposive sampling method. The total number of samples is 80 data. The data is obtained from the company's financial reports, which have been published on IDX's official website and each company's website. Data processing in this study was assisted by Microsoft Excel and SPSS version 25.0. Multiple linear regression analysis method is used in this study. The results of the partial test in this study are earnings per share, current ratio, debt to equity ratio, and return on equity have no effect on firm value, while net profit margin has a negative effect on firm value. Simultaneous test results in this study indicate that earnings per share, current ratio, debt to equity ratio, return on equity, and net profit margin significantly affect abnormal returns, indicating a weak indication of early release of information.